2012
DOI: 10.5897/ajar09.636
|View full text |Cite
|
Sign up to set email alerts
|

Economic appraisal of small and medium scale performance in poultry egg production in Ogun State, Nigeria

Abstract: The study was carried out majorly to appraise economically the performance of poultry egg farmers by scale in Ogun State, Nigeria. Specifically, the study examined cost structure and profit level in the industry at different scale levels as well as the factors that determine the revenue of the poultry egg farmers. Purposive sampling procedure was used to select 50 representative poultry egg producer from whom primary data were obtained. The results of data analysis showed that costs of feed constituted the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The first criterion considered in the present study was the profit criterion. Oladeebo et al (2012) investigated the factors that affect the profit criteria in the egg industry in their study conducted in Nigeria. These authors have found that there is an important relationship between profits and scales of eggproducing enterprises, and medium-sized enterprises are more profitable with the rates between 40.0% and 73.0% than small-scale enterprises.…”
Section: Resultsmentioning
confidence: 99%
“…The first criterion considered in the present study was the profit criterion. Oladeebo et al (2012) investigated the factors that affect the profit criteria in the egg industry in their study conducted in Nigeria. These authors have found that there is an important relationship between profits and scales of eggproducing enterprises, and medium-sized enterprises are more profitable with the rates between 40.0% and 73.0% than small-scale enterprises.…”
Section: Resultsmentioning
confidence: 99%